Weed seedbank characteristics of arable fields under different fallow management systems in the humid tropical zone of southeastern Nigeria - Akobundu, I.O.; Ekeleme, F. (Springer, 2002)
The composition and pattern of weed flora in arable fields are determined by their seedbank structure; but the influence of fallow management practices on weed seedbank structure is presently unknown. The objective of this study was to investigate weed seedbank characteristics and weed population dynamics in arable fields in natural and planted-fallow systems. The study plots were at Mbaise, a densely populated area of southeastern Nigeria, where farmers regenerate their exhausted soils by maintaining planted fallows of Dactyladenia barteri (Hook. F. ex Oliv.) Prance & F. White, and at Umuahia, a less-densely populated area in the same region, where farmers depend on natural bush fallow for soil regeneration. The effect of three years of fallow on the weed flora of arable fields in the two fallow management systems differed remarkably. The first flush of weeds on fields that were cultivated after three years of planted D. barteri fallow (Mbaise) consisted of 80% broadleaf weeds, 7% grass weeds and 13% sedges. On the other hand, the first flush of weeds on the natural bush fallow fields (Umuahia) of the same fallow duration as the D. barteri fallow system consisted of 17% broadleaf weeds, 70% grasses and 13% sedges. Three years of planted fallow caused 36% decrease in weed seedbank at Mbaise relative to the cropped field while the same duration of natural bush fallow caused a 31% increase in weed seedbank at Umuahia. These results show that the planted D. barteri fallow system has a higher potential to reduce weed pressure in smallholder agriculture than the natural bush fallow system and may explain in part why farmers in this humid forest zone have adopted the practice.